2021
DOI: 10.3389/fpubh.2021.616014
|View full text |Cite
|
Sign up to set email alerts
|

Health Seeking Behavior Among Adults and Elderly With Chronic Health Condition(s) in Albania

Abstract: Aim: Assess the use of different health care service providers by adults (aged 18–59) and elderly (aged > =60) who suffer from non-communicable disease (NCD) and explore relationships between sociodemographic variables and care-seeking behaviors.Methods: A cross-sectional survey was conducted in the districts of Diber and Fier in December 2018, using random cluster sampling. Descriptive statistics were used to compare the care-seeking behaviors of adults and elderly people. We employed binary and multin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 27 publications
(53 reference statements)
1
34
0
1
Order By: Relevance
“…This has been reported by many studies including that education significantly influenced health seeking behavior among the older people thus influencing their health status. [2,17,18] Income which coincide with the purchasing power of the elderly people was also found to significantly influenced their health status. Poverty especially in LMICs in Africa has been found to be a major barrier to seeking treatment among the older people whenever they are sick.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This has been reported by many studies including that education significantly influenced health seeking behavior among the older people thus influencing their health status. [2,17,18] Income which coincide with the purchasing power of the elderly people was also found to significantly influenced their health status. Poverty especially in LMICs in Africa has been found to be a major barrier to seeking treatment among the older people whenever they are sick.…”
Section: Discussionmentioning
confidence: 93%
“…This result is in agreement with in their work on health seeking behavior among adults and elderly with chronic health condition(s) who found that considerable proportions of the elderly people in low and middle income countries (LMICs) suffered from chronic health condition. [17] In addition, [18] in their work on multimorbidity and health seeking behaviours among older people in Myanmar: A community survey found that considerable proportions of the elderly people reported at least one chronic condition with about 33.2% reporting two or more conditions (multimorbidity). This is an indication that ageing is associated with both intrinsic and extrinsic changes as well as health problems with varying levels of disability and limitations in functionality.…”
Section: Discussionmentioning
confidence: 99%
“… 14 16 , 20 Women who live in urban settings have good health-seeking behavior and might have better access to maternal health care services, such as antenatal care (ANC). 21 , 22 The study done in Northeast Ethiopia showed that ANC service utilization has positive significant association with the knowledge of the vertical transmission of HIV. 23 Another reason might be due to the inter-regional and rural–urban differentials in access to education and resources, including HIV and AIDS education.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies documented health-seeking behaviors among the persons with poor health conditions. For example, a cross-sectional survey in Albania concluded public facilities were reported as the main health care service providers by adults with non-communicable diseases [ 15 ]. An Australian cohort demonstrated that persons with hypertension and poor self-rated health were likely to visit frequent monthly general practitioners [ 16 ].…”
Section: Introductionmentioning
confidence: 99%